Análisis del capital social de los productores agroecológicos de la provincia de Tungurahua, Cotopaxi 2021-2022. - Huilcamaigua Siza, Ligia Maribel (2022)
The objective of this research work is to carry out an analysis of the social capital of agroecological producers in the province of Tungurahua in times of pandemic by COVID-19, a disease that globally harmed the world economy, therefore all sources of income. jobs, as well as agroecological production based on the Organic Law of the Food Sovereignty Regime. For which the recognition of the place and the zoning in different cantons of Tungurahua were carried out: Pelileo, Ambato, Pillaro, Quero, Tisaleo. Subsequently, the study technique is applied, such as the survey with the use of a digital form on the GOOGLE FORMS platform based on social indicators (internal management, organizational status, institutionality, legalization and autonomy), thus knowing the current reality of each producer and the different associations, through the qualitative and quantitative modality, since the quantitative data helped to observe the general panorama, while the qualitative data provided detailed information that contributes in a personal way to the results of the survey. Complemented with exploratory and field research, having an approach to the research problem, which was given with the participation of the 140 producers as respondents. Obtaining as results of the analysis, the identification of the critical points in the social capital of the "PACAT", through the use of a tabulation of a simple statistical analysis in Excel, multivariate principal components analysis and a conglomerate analysis. Resulting in the most critical point in the strategies that they make to realize in the market with a general average of 0.24 and in the percentage of the survey it reveals that none uses any type of strategies with 25%. This reflects the lack of training in different types of strategies, the same ones that it would be advisable to impart in the training that partners constantly receive focusing on this topic.